Das alltägliche Drama: Luigi Nonos Vokalkompositionen mit Tonband La fabbrica illuminata und A floresta é jovem e cheja de vida im Kontext der unvollendeten Musiktheaterprojekte 2 vols. - Jozefowicz, Nina (Hofheim Wolke, 2012)
Following his first stage work Intolleranza in 1960, the composer Luigi Nono (1924-1990) radically changed his compositional practice: A fixed score was replaced by improvisation on text and sonic experimentation in the recording studio. La fabbrica illuminata and A floresta é jovem e cheja de vida thus belong to a series of vocal compositions that are closely linked to Nono's direction of the performance as sound director and the performers of the time - singers, actors from the American The Living Theatre and the Milan Piccolo Teatro as well as instrumentalists. They mark the beginning of a pioneering development in the Venetian composer's oeuvre, the effects of which can be traced right through to his late works. The effects of this can be traced right through to the late works.The book is aimed at scholars as well as performers and anyone interested in learning more about Nono's working methods. Transcriptions and illustrations of numerous autograph documents from various Italian private archives as well as theatre and radio archives provide a well-founded insight into the composer's approach. For the first time, it has been possible to present a detailed account of the genesis of the two compositions, which are closely linked to a music theatre project. The final chapter contains important information on today's performance practice as well as background information that is important for a new production of the works. (Translated with Deepl.com)
Keywords: Nono, Luigi -- 1924-1990; Music theater